HARMONY BETWEEN JAVANESE, SUNDANESE, AND BATAK ETHNICS IN BABUSSALAM VILLAGE, MARBAU SUB-DISTRICT, NORTH LABUHAN BATU RRGENCY - Nurul meili Fanny; Husaini Husda; Munawiah (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
This study aims to determine what causes the peace in Babussalam Village, how the three ethnic groups Javanese, Sundanese, and Batak maintain peace in society, and how social interaction between the Javanese, Sundanese, and Batak ethnic groups occurs in Babussalam Village. This study employs a qualitative, descriptive research design. This study used observation, interviews, and documentation as its methods. The findings of this research are: the background of harmony in Babussalam Village is influenced by a number of elements, including those in the social and economic, educational, and religious spheres. Respect, freedom of expression, cooperation, positive prejudices, and fostering a welcoming environment are all important for preserving harmony in a community where these three ethnic groups coexist. Due to the fact that people are social beings who cannot survive alone and require the assistance of others, the social interaction in Babussalam Village is highly positive.